(3GdSjGSI GdLfGFjI dfbd hRQGYI GdCYVGA (B: s (3OQGSI ebGQfI (B/ s - (3ajUd SYOhf GdeWjQj s; (3YeQ eMeO eMeO SGde (B: s ((3GdbGgQI (B: s (3ajUd SYOhf GdeWjQj (B: s, 2017)
(3JYO egfI GdWH ef CfHd Gdegf(B: (3agj EfSGfjI aj ZGjJgG GdeJeKdI aj GdSYj Edi GdMaGX Ydi Mb GdCaQGO aj GdMjGI hSdGeI CLSGege(B: (3hGdJNaja ef eYGfGJge Vef GMJQGe MjGI GdaQO hcQGeJg GdEfSGfjI Ohf JejjR(B: (3hdJMbjb Pdc cQS GdHGMKhf ChbGJge hLghOge dJWhjQ GdWH(B: (3GdPj gh cZjQg ef GdYdhe aj JbOe eSJeQ(B: (3MJi Cf GdWHjH jYLR Yf edGMbI GdJWhQ GdMGUd aj gPG GdejOGf hGSJjYGHg(B. (3hCge eG jejR gPG GdJWhQ hGdJbOe gh JLGhR GdCYeGd GdWHjI GdJbdjOjI(B: (3HXghQ hSGFd afjI CcKQ aYGdjI aj GcJTGa GdMGdGJ GdWHjI hYdGLgG(B: (3Ch GdhbGjI efgG(B. (3heeG gh LOjQ HGdedGMXI Cf GdfUa GdKGfj ef GdbQf GdYTQjf TgO JWhQkG ePgdkG aj GdYdhe GdWHjI(B: (3hGdYOjO ef GdEfLGRGJ GdYdejI aj gPG GdeLGd(B. (3hdYd Cge hCYXe eG JMbb HGdfSHI dMjGI GdEfSGf hUMJg gh GdJdbjM GdGUWfGYj(B: (3hJZjjQ GdLfS hGdGSJfSGN(B: (3hcPG GfJTGQ YedjGJ fbd hRQY GdCYVGA GdHTQjI(B. (3hJYJHQ gPg GdCNjQI ef CHQR GdehGVjY GdWHjI hCgegG deG JdYHg ef OhQ cHjQ aj EfbGP GdeQVi GdegOOI MjGJge HGdehJ GdeDcO(B: (3EP CUHM ef Gdeecf fbd CYVGA CLRGA efgG ef TNU Edi BNQ(B: (3ShGA cGf GdChd MjkG Ch ejJkG(B. {u(32003(B} s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdSjGSI GdLfGFjIs; (3GdWHs; (3fbd hRQGYI GdCYVGAs